Effect of different types of therapeutic trauma on vitiligo lesions. Issue 2 (20th December 2016) - El Mofty, Medhat; Esmat, Samia; Hunter, Nahla; Mashaly, Heba M.; Dorgham, Dina; Shaker, Olfat; Ibrahim, Sarah
Abstract: New treatment modalities for vitiligo acting by changing certain cytokines and metalloproteinases are newly emerging. The aim of this work is to To assess the efficacy of trichloroacetic acid (TCA) chemical peel, dermapen, and fractional CO2 laser in treatment of stable non‐segmental vitiligo and to detect their effects on IL‐17 and MMP‐9 levels. Thirty patients with stable vitiligo were recruited in a randomized controlled study. They were randomly categorized into three equal groups. Group 1: TCA peel, Group 2: dermapen machine, and Group 3: Fractional CO2 laser. Skin biopsies were taken from treated areas and from control areas for which MMP‐9 and IL‐17 tissue levels were measured using ELISA. The 30 vitiligo patients had low basal tissue MMP‐9 levels and high baseline IL‐17 tissue levels. As regards the three different used modalities, all of them caused rise in MMP‐9 as well as IL‐17 levels and almost their levels were much more elevated with repetition of the previously mentioned traumatic procedures. TCA 25% peel proved to be the most effective modality both clinically and laboratory and it can be used prior or with other conventional therapies in the treatment of vitiligo.